Identificação e diversidade genética de rotylenchulus reniformis em áreas de cultivos de meloeiro (cucumis melo l.) - Barreto, Alcileide Vieira (Universidade Federal Rural do Semi-Árido, 2018)
ABSTRACT This research aimed to identify through microscopic and molecular analyzes the presence of the nematode Rotylenchulus reniformis in different melon producing areas and verify the genetic diversity. Soil samples were collected from five farms in the state of Rio Grande do Norte (Dinamarca, Brazil Melon, CY Matsumoto, Itaueira and Agrícola Famosa) and one from Ceará (Mata Fresca). Thirty soil samples were collected in different areas of each farm, which were taken to greenhouse and sown with Vedrantais melon. After 35 days of sowing, the plants were collected, and their roots submitted to the staining process for microscopic identification of R. reniformis. The DNA of the roots of the melon was extracted aiming the molecular analyzes with the universal primers for nematodes and genes specific for R. reniformis. For the genetic diversity study, R. reniformis was isolated from suspensions of soil samples under an optical microscope. Then the DNA from them was extracted through the NucleoSpin Tissue (Macherey-Nagel) ® extraction kit. DNA analyzes were performed from the screening of 20 RAPD primers. The data generated were analyzed by the Genes program. Of the 22 root samples evaluated microscopically, only three showed the presence of R. reniformis females. Regarding the molecular analyzes with the universal primer, 15 areas belonging to five farms were positive for the presence of nematode DNA. The analyzes with specific genes primers revealed that six areas, restricted to two farms (Itaueira and Mata Fresca), were confirmed with the presence of R. reniformis. Only nine of the 20 RAPD primers were selected for diversity analysis, which generated 67 polymorphic bands (95.71%) and three polymorphic bands (4.29%), thus evidencing a high polymorphism, with an average of 7.4 bands polymorphic by primer. The primer with the highest number of polymorphic bands was OPAA-04 with 11 bands whereas OPA-03 was the primer with the lowest number (5). A dendrogram was constructed using the UPGMA hierarchical method. Using a cutoff of 0.55, two groups were found. The first one, was formed by the farms Itaueira and Mata Fresca and the second group by the other farms. The estimates of cophenetic correlation, stress and distortion indicated that the grouping was efficient and with little loss of information. For the dendrogram obtained from 51 R. reniformis samples, the formation of six groups was observed. The largest group formed was V, contemplating 34 samples, approximately 66.7%. The cofenética correlation was estimated at 0.77%. It was found that the study did not indicate any association between the magnitudes of dissimilarities and the origin of the samples. It was verified that the largest (0.92) and the lowest (0.27) value of similarity was found among samples belonging to Fazenda Itaueira. The study indicates that there is variability between samples with a mean dissimilarity coefficient of 0.63 and a coefficient of variation of 14.88%. This is the first genetic variability study with molecular markers performed with samples from the production fields of the main melon exporting region in Brazil
Keywords: Nematoide; RAPD; Variabilidade genética; Nematode; RAPD; Genetic variability; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE